Pemanfaatan Grup WhatsApp dalam Pembelajaran Online di Masa Pandemi COVID-19 - Andi Badli Rompegading; Rizky Arfadilla; Ayu Muliana; Ahmad Ghazali; Rizal Irfandi (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to learn about using the WhatsApp application in online learning during the COVID-19 pandemic. The method used is Traditional Review. The results showed that WhatsApp was useful in bridging the communication gap between lecturers and students during the e-learning process and cost-effective, easy and practical to use. In conclusion, the use of the WhatsApp application tends to get a positive response, so it has an important role in the world of education during the COVID-19 pandemic. Keywords: COVID-19, Online Learning, WhatsApp